Spatiotemporal patterns of gross ecosystem product across China's cropland ecosystems over the past two decades - Zhang, Jiaying; Song, Yang; Wang, Jing (Frontiers in Ecology and Evolution, 2022)
As the largest artificial ecosystem on Earth, croplands not only secure the basic living materials for people but also provide ecological service values for human society. For croplands, ecosystem services have proven to be of great value and are closely linked to human activities and climate change. However, spatio-temporal patterns of cropland ecosystem services and their drivers still need to be further assessed quantitatively. Here, we provide a comprehensive evaluation of ecosystem services across China’s cropland ecosystems over the last two decades using the gross ecosystem product (GEP) approach. The values of material services, regulating services, and cultural services were calculated to summarize the GEP value of cropland ecosystems in China. Our results showed that the GEP value was different among provinces, leading to a heterogeneous spatial pattern associated with population and cultivated area. Moreover, we analyzed the trends in the GEP value at the provincial and national scales. The results showed that the GEP value of China’s cropland ecosystems has increased over the period. The majority of provinces had an increasing trend in GEP, yet some developed provinces, e.g., Beijing and Shanghai, showed a decreasing trend. Furthermore, we evaluated the impacts of social-economic and natural factors on changes in GEP. We found that rising prices for agricultural products and services boosted an increase in GEP. Meanwhile, the spatio-temporal patterns of GEP were also associated with the adjustments of planting area in each province. Overall, our findings highlight the importance of assessing spatio-temporal patterns of cropland ecosystem services for decision-makers.